Homonymous hemianopsia - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Homonymous hemianopia (HH) is a visual field defect involving either two right or the two left halves of the visual field of both eye. It results from the damage of the visual pathway in its suprachiasmatic part. The causes of HH include stroke, brain tumors, head injuries, neurosurgical procedures, multiple sclerosis and miscellaneous conditions. HH result in a severe visual impairment and affect a variety of cognitive visual functions. Patients with HH frequently have difficulties with reading and scanning scenes in sufficiently rapid fashion to make sense of things as a whole. They stumble, fall or knock objects in their surroundings, since they cannot see them and they are frequent surprised that somebody or something suddenly appeared in their visual field. The prognosis of visual field deficit recovery is highly variable and depends on the cause and severity of brain and optic pathway injury. The fundamental method in the management of HH patients is rehabilitation. Rehabilitation techniques used in HH include three groups of methods: optical therapies, eye movement-based therapies, and visual field restitution therapies.